1997
DOI: 10.1037/0278-7393.23.4.932
|View full text |Cite
|
Sign up to set email alerts
|

The role of examples and rules in the acquisition of a cognitive skill.

Abstract: In 3 experiments, participants memorized 8 examples, each exemplifying a different rule. Participants were asked to extend these rules to new examples. They practiced applications of the rules to examples over a period of 4 days (Experiment 1) or 5 days (Experiments 2 and 3). Although these rules were bidirectional, an asymmetry gradually built up such that participants became more facile in using the rules in the practiced direction. Participants also showed an advantage when the initial study example was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
188
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(207 citation statements)
references
References 19 publications
(38 reference statements)
9
188
6
Order By: Relevance
“…It remains an open question, then, whether a qualitative process shift similar to that demonstrated here occurs in the case of recognition memory practice. Anderson et al (1997) found evidence for transfer of cued-recall retrieval practice to inverted items using a very different task than ours. They had subjects study items such as "Skydiving was practiced on Saturday at 5 p.m. and on Monday at 4 p.m." For each sport there was a rule to be discovered.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…It remains an open question, then, whether a qualitative process shift similar to that demonstrated here occurs in the case of recognition memory practice. Anderson et al (1997) found evidence for transfer of cued-recall retrieval practice to inverted items using a very different task than ours. They had subjects study items such as "Skydiving was practiced on Saturday at 5 p.m. and on Monday at 4 p.m." For each sport there was a rule to be discovered.…”
Section: Discussioncontrasting
confidence: 56%
“…Instead, it simply improves access to, or strengthens, the originally encoded episode, resulting in speedup and, potentially, even a drop of episodic retrieval from conscious awareness. Closely related ideas are embodied in several recent proposals in the literature (Anderson, Fincham, & Douglass, 1997;Crutcher & Ericsson, 2000;Pirolli & Anderson, 1985;Rabinowitz & Goldberg, 1995). As a concrete example, consider the case of semantically based mental imagery that is studied in Experiment 1.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…They may do so, for instance, (1) by retrieving a previously acquired, but perhaps not fully learned, production rule or schema, (2) by reasoning by analogy to a prior example in memory or in the tutor's glossary, or (3) by interpreting and applying a textbook rule or a tutor hint message (c.f., Anderson et al 1997).…”
Section: Unpacking the Process: What Causes Load In Tutored Problem Smentioning
confidence: 99%
“…The heuristic-based information-processing models of Simon and Newell (1971) recognize analogy as an important strategy for searching in a problem space. 3 Similarly, analogical mapping has been incorporated in Anderson's ACT-R cognitive architecture as a potential mechanism for constructing new production rules 4 (J. R. Anderson, Fincham, & Douglass, 1997;Salvucci & Anderson, 2001). …”
Section: Cognitive Tools For Uncertaintymentioning
confidence: 99%